A Biography of the Pixel, Alvy Ray Smith (2021). Issue 2 (1st October 2021) - Heller, Lynne
Review of: A Biography of the Pixel, Alvy Ray Smith (2021)Cambridge, MA: The MIT Press, 560 pp., ISBN 978-0-26254-245-6, p/bk, 39.95